Fetomaternal outcome in high-risk parturients receiving epidural analgesia using fentanyl with ropivacaine versus iv tramadol: a comparative study - Taneja, Ashima; Arora, Kamaldeep; Chopra, Isha; Grewal, Anju; Naik, Sushree Samiksha; Sharma, Geetika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Labour analgesia has been recommended but sufficient data on use of labour epidural analgesia with ropivacaine and fentanyl combination during labour is not available. Methods: A comparative study was conducted on 40 high risk labouring partuirents, randomly allocated to group A (iv tramadol) and group B (epidural analgesia with ropivacaine plus fentanyl). Assessments were done for fetal heart rate abnormality, mode of delivery, duration of labour, and Apgar score. The VAS score, patient satisfaction score, and complications were recorded. Results: Group A had more number of instrumental deliveries compared to group B, the later had higher number of caesarean sections. No difference was observed in vaginal deliveries in both the groups. Pain relief was significant in patients of epidural group. The neonatal outcome was same in both the groups. Significant number of patients had a higher degree of satisfaction score in group B compared to group A. Conclusions: Tramadol and epidural analgesia in labour are safe and effective. Patient satisfaction is significantly higher in epidural group as compared to the tramadol group.